Assessment of Drug Utilization and Adequacy of Analgesics Usage among Postoperative Patients in Orthopedics Department in a Tertiary Care Hospital-A Prospective Observation Study - Jyoshna, Belum; Chandu, Vadlavari Pavan; Sai, Valmiki Uday; Reddy, Gaddam Vamsidhar; Supraja, Bandi Sai; Shankar, Caleerappa Ravi; Sudheer, Akkiraju (International Journal of Pharmaceutical Investigation, 2025)
Background According to WHO Drug Utilization research, it is defined as "the marketing, distribution, prescription, and use of drugs in a society, with special emphasis on the resulting medical, social, and economic consequences." Effective postoperative pain management is crucial to improve patient care outcomes after surgical intervention. The current study aimed to assess the utilization of analgesics and determine the most commonly prescribed analgesic for postoperative pain management. The study also aimed to evaluate the intensity of pain and the adequacy of analgesic use. Materials and Methods A hospital-based prospective observational study of 133 patients was conducted over a period of 6 months in the Department of Orthopedics at KIMS SAVEERA Hospital in Anantapur, Andhra Pradesh, India. Results On Day 0, 1, 2, and 3, the majority of participants were administered Inj. Diclofenac 75 mg. However, on Day 3, the number of participants prescribed Tab. Aceclofenac 100 mg+Paracetamol 325 mg increased. Adequate pain management was observed in 55.6% of patients on POD-0, which increased to 82.7% and 100% on POD-1 and POD-2, respectively, showing statistical significance. Conclusion The study concluded that NSAIDs, particularly diclofenac, were the most commonly prescribed analgesics for postoperative pain relief. The average number of drugs prescribed per encounter was high (4.6), and the percentage of drugs prescribed by generic name and from the Essential Medicine List were lower (21.3% and 31.6%, respectively) compared to WHO standards. It is recommended that drugs be prescribed by generic names rather than brand/trade names, and healthcare providers should be educated on the essential list of medicines and encouraged to adhere to rational prescribing practices.
Keywords: Analgesics; Orthopedics; Drug Utilization; Pain intensity